2016
DOI: 10.1016/j.renene.2016.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Wave energy potential along the Atlantic coast of Morocco

Abstract: This study analyses the wave energy resource along the Atlantic coast of Morocco using a 44-year series of data obtained from numerical modeling (hindcasting). The spatial distribution of wave power is analyzed using data from 23 points along that coast. The estimated resources (average wave power up to 30 kW/m and average annual wave energy up to 262 MW h/m) are considerable and slightly lower than at the neighboring Canary Islands. The central part of this area (between latitudes 29°30'N and 34°N) is the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 45 publications
1
40
1
1
Order By: Relevance
“…Thus [29] found at the Mediterranean Coast of Morocco wave energy powers between 2 kW/m and 6 kW/m, while [30] estimated a mean wave power of 6.3 kW/m at a point in the Moroccan Mediterranean. The results obtained by Sierra et al [6] from the average power of the waves is important (up to 30 kW/m with an annual energy average waves up to 262 MWh/m) on the Atlantic coast. Nevertheless, as far as the authors know, there are no specific studies addressing the potential of tidal energy there.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus [29] found at the Mediterranean Coast of Morocco wave energy powers between 2 kW/m and 6 kW/m, while [30] estimated a mean wave power of 6.3 kW/m at a point in the Moroccan Mediterranean. The results obtained by Sierra et al [6] from the average power of the waves is important (up to 30 kW/m with an annual energy average waves up to 262 MWh/m) on the Atlantic coast. Nevertheless, as far as the authors know, there are no specific studies addressing the potential of tidal energy there.…”
Section: Resultsmentioning
confidence: 87%
“…Until now, despite its great potential for wind and solar energy, only 10% of Morocco's energy production comes from renewable sources, mainly hydro and wind. Sierra and co-workers [6] have found that the average power of the waves is important, with an annual energy 30 kW/m in Atlantic coast.…”
Section: Introductionmentioning
confidence: 99%
“…(Panicker N. N., 1976) In the field of potential wave calculation, studies have been carried out around the world such as the potential of wave power on the Moroccan Atlantic coast, the wave energy potential of the French Atlantic coast and the potential use of wave energy in South Africa. These calculations illustrate that the highest and lowest wave power on the Moroccan Atlantic coast is 29.94 kW/m with a depth of 45 m and 7.83 kW/m with a depth of 47 m. (Sierra, J. P, 2016) For the French Atlantic coast, these values are maximum 42.56 kW/m and minimum 7.19 kW/m in the depth of water 89 m and 30 m respectively. (White A., 2016) These values were also obtained for the coasts of South Africa at about 22 kW/m as the maximum wave power and approximately 8 kW/m as the minimum wave power.…”
Section: Introductionmentioning
confidence: 78%
“…where is a coefficient whose value depends on the shape of the wave spectrum (0.86 for a Pierson-Moskowitz spectrum and increasing towards unity with decreasing spectral width) [21]. In the spectrum formulation, it is assumed that the wind is blowing steadily for a long time and over a large area such that the waves attain a point of equilibrium with the wind.…”
Section: Theoretical Backgroundmentioning
confidence: 99%